Integração da atenção básica e especializada à saúde em municípios rurais do Oeste do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
The integration between Primary and Specialized Care in remote rural municipalities in Brazil faces significant challenges, compromising equity and the effectiveness of the Unified Health System (SUS). This study analyzed the main structural, logistical, and administrative barriers to accessing specialized care, with an emphasis on pharmaceutical assistance and the counter-referral process between healthcare levels. A qualitative study was conducted in five municipalities in western Pará, using interviews with healthcare professionals and municipal managers to understand difficulties in accessing specialized services. The results highlighted problems such as poor communication between primary and specialized care, long waiting lists, difficulties in sanitary transportation, and inadequate infrastructure in primary healthcare units. Additionally, weaknesses in pharmaceutical assistance management were identified, including shortages of essential medicines, deficiencies in stock control, and the absence of pharmacists in the multidisciplinary team. Overcoming these challenges requires public policies aimed at expanding healthcare infrastructure, improving transport, strengthening pharmaceutical assistance, and adopting technologies to optimize patient regulation and follow-up. It is concluded that strategies such as digital pharmaceutical management, and strengthening primary care can contribute to greater service resolution and better integration between healthcare levels.
Keywords: Assistência farmacêutica; Infraestrutura; Saúde rural; Logística em saúde; Contrarreferência; CNPQ:: CIÊNCIAS DA SAÚDE